When is birthweight at term abnormally low?: a systematic review and meta-analysis of the association and predictive ability of current birthweight standards for neonatal outcomes - Malin, G.L.; Morris, R.K.; Riley, R.; Teune, M.J.; Khan, K.S. (Wiley ( Commercial Publisher ), 2014)
Background Intrauterine growth restriction is a cause of neonatal morbidity and mortality. A variety of definitions of low birthweight are used in clinical practice, with a lack of consensus regarding which definitions best predict adverse outcomes.